A Transcriptomic Signature of Depressive Symptoms in Late Life - Stuart Matan-Lithwick; Melissa C. Misztal; Mu Yang; Thomas DeLong; Shreejoy Tripathy; Jeffrey T. Dunn; David A. Bennett; Philip L. De Jager; Yanling Wang; Daniel W. Fisher; Hongxin Dong; Daniel Felsky (Biological Psychiatry Global Open Science)
Background: Depressive symptoms in late life can impair daily function and accompany cognitive decline. However, the molecular mechanisms that underlie these changes in the brain remain poorly understood. Methods: Differential expression analysis was performed on bulk-tissue RNA sequencing data generated from dorsolateral prefrontal cortex samples of elderly participants in ROS/MAP (Religious Orders Study and Memory and Aging Project; N = 998, mean age at death = 89.7 years). Bulk tissue RNA sequencing was analyzed against depressive symptoms measured prior to death, controlling for Alzheimer’s disease neuropathology, medication status, and lifestyle factors. Sex-stratified models were also tested. Results: Increased abundance of the Prader-Willi syndrome–associated gene PWAR1 (corrected p = 5.47 × 10−3) and CTDSPL2 (corrected p = .03) were associated with a higher burden of depressive symptoms in the combined sample. An additional 14 genes showed suggestive associations, including several with known links to neuropsychiatric illness (e.g., ACVR2B-AS1, COL19A1). Functional enrichment analysis revealed downregulation of aerobic metabolism and upregulation of both amino acid catabolism and DNA modification processes. Differential expression signatures were poorly correlated between males and females (Pearson r = 0.12; 95% CI, 0.10 to 0.13), and only the male group showed independently significant differential expression. Little overlap was found with previously published analyses of major depressive disorder. Conclusions: Building on recently published single-nucleus profiling, we present the largest-ever study of transcriptomic correlates of depressive symptoms in late life, revealing new insights into sex-specific regulators. PWAR1 and CTDSPL2 were identified as putative markers of late-life depression in the dorsolateral prefrontal cortex and warrant further study.